Control previo y la ejecución presupuestal de la Municipalidad Distrital de Belén 2025 - Torres Pinchi, Jany Stephanie (2025)
The purpose of this research was to determine how prior control is related to budget execution in the Belen 2025 District Municipality. Deciding on a basic study, the sample consisted of 60 municipal employees. A questionnaire was used to conduct the survey. The findings show that prior control is "good" at 46.7%; budget execution is rated "good" at 50.0%. Therefore, the variables are found to have a significance level of p=0.000. Likewise, the dimension of prior control implementation shows a significance level of p=0.000; likewise, the dimension of risk assessment and prevention shows a significance level of p=0.000; and finally, the dimension of risk management control shows a significance level of p=0.000. These dimensions are positively and significantly related to budget execution.